Deteksi Keaslian Uang Rupiah Menggunakan Metode Canny Edge Detection dan K-Mean Clustering - Selvana Fadila; Dedy Abdullah (Progresif: Jurnal Ilmiah Komputer, 2025)
The escalating problem of counterfeit currency in various countries, primarily due to easy access to information on manufacturing methods and advancements in color printing technology, renders traditional '3D' identification methods less effective. This research aims to design an authenticity detection system for Rupiah banknotes using a digital image processing approach. This study utilized a total of 40 Rupiah banknote images as test objects, comprising 10 genuine and 10 counterfeit images for each of the Rp 50,000 and Rp 100,000 denominations. The methodology applied included image acquisition, conversion to grayscale, followed by image segmentation. This system integrates Canny Edge Detection to extract edge details and K-Means Clustering for image grouping. Key features analyzed were Aspect Ratio and Edge Density, which assist in differentiating between genuine and counterfeit banknotes. Test results indicate that the developed system could identify the authenticity of Rupiah banknotes with an average accuracy of 87.50%. This combined approach offers an effective solution for Rupiah banknote authentication.Keyword: Authenticity Rupiah Banknotes; Canny Edge Detection; K-Means Clustering; Aspect Ratio, Edge Density. AbstrakPermasalahan uang palsu yang terus meningkat di berbagai negara, terutama dengan kemudahan akses informasi dan teknologi pencetak warna, menjadikan metode identifikasi tradisional '3D' kurang efektif. Penelitian ini bertujuan untuk merancang sebuah sistem deteksi keaslian uang kertas Rupiah menggunakan pendekatan pengolahan citra digital. Penelitian ini menggunakan total 40 citra uang kertas Rupiah sebagai objek uji, terdiri dari 10 gambar uang asli dan 10 gambar uang palsu untuk masing-masing nominal Rp 50.000 dan Rp 100.000. Metodologi yang diterapkan meliputi akuisisi citra, konversi citra menjadi skala abu-abu, diikuti dengan segmentasi citra. Sistem ini mengintegrasikan Canny Edge Detection untuk mengekstraksi detail tepi dan K-Means Clustering untuk pengelompokan citra. Fitur-fitur kunci yang dianalisis adalah Aspect Ratio dan Edge Density, yang membantu dalam hal membedakan uang asli dan palsu. Hasil pengujian menunjukkan bahwa sistem yang dibangun mampu mengidentifikasi keaslian uang Rupiah dengan akurasi rata-rata sebesar 87.50%. Pendekatan gabungan ini memberikan solusi efektif untuk autentikasi uang kertas Rupiah.Kata kunci: Keaslian Uang Rupiah; Canny Edge Detection; K-Means Clustering; Aspect Ratio; Edge Density.